Model Triple Bottom Menuju Kinerja Keuangan - Hermanto Hermanto (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2021)
The study conducted to identify effect of Sustainability Report, Environmental Performance-GRI200, Economic Performance-GRI300, and Social Performance-GRI400 related to Return on Assets in organizations included in the ASSRAT nominations for 2017-2019 both together and individually. Judgment sampling sampling method. The sample of this research is 20 corporate entities included in the ASSRAT nomination and registered on the Indonesia Stock Exchange (IDX) with a sample of 60 data. The type of data is secondary from sources of financial information and annual reports. Multiple linear regression analysis method. The findings of this study are based on the results of the f test, the independent variable has a simultaneous effect on Return on Assets. Partially Environmental Performance- GRI 200 and Economic Performance- GRI 300 have a positive impact on Return on Assets, Companies that are included in the ASSRAT nomination pay more attention to aspects of the company's Economic Performance so that the old Corporate Relations paradigm is still adopted by companies that are nominated by ASSRAT. Companies in the ASSRAT nomination do not only pay attention to profits but also pay attention to aspects of environmental performance so that they can improve the company's image in the eyes of stakeholders.